Punishment and Authority in the Athenian Forensic Discourse. - Kucharski, Janek (Scripta Classica Israelica, 2024)
Authority is a presupposition built into the modern concept of punishment, both in terms of its moral or legal justification, as well as language. Its lack not only raises questions about the justice of harming an offender for an offence, but also about the felicity of labeling such an act as punishment. In the ancient Athenian forensic discourse, however, punishment was not a distinct notional category. It was a concept superimposed on several other terms, each with its own semantic domain extending beyond the punitive sphere. It has been argued, nonetheless, that authority was a fundamental criterion of this concept, one, which distinguished the sense of "punishment" from other possible meanings of the relevant vocabulary. Indeed, when it came to legal offences, the orators showed a keen awareness that punishment was an exclusive prerogative of the state and its institutions. Yet on the level of discourse, they seem no longer interested in maintaining this distinction, as they frequently speak of punishment meted out to offenders by non- authoritative agents, such as the prosecutor. This paper argues that the question of authority, although legally recognised, never entered the framework which shaped the discourse of punishment in classical Athens.